Teacher beliefs and practices in communicative language competence towards the development of an autonomous learning model - Dwee, Chiew Yen (2017)
There is great impetus for English courses in institutions of higher learning (II-IL) at present due to its functional importance as a tool for individual and national development, graduate employability and life-long learning. However, it remains a common complaint among employers that Malaysian fresh graduates lack English proficiency and critical thinking skills. Thus, this qualitative study sets out to examine the focus and emphasis on English language proficiency, critical thinking skills and study skills of five (5) English courses offered by Universiti Tun Hussein Onn Malaysta (UTHM) through semi-structured interviews, classroom observations and document analysis. The interviews conducted with five teachers and ten students were transcribed using Transana software before being coded for analysis. A grounded theory approach which emphasises on several stages of data collection and constant comparison of data was employed to interpret the data. The main findings revealed that teachers in general \· think that language proficiency, critical thinking and study skills are important for tertiary level English classrooms. However, actual teaching practices were found to differ from the teachers' beliefs towards critical thinking and study skills due to challenges which can be categorised as teacher factors, student factors and institutional factors. Finally, several important criteria were identified from the findings to form an autonomous learning model for English language communicative competence called the SITE Model. The findings of this study especially the current beliefs and teaching practices of teachers as well as the proposed SITE Model may serve as a reference point for researchers, educators and policy makers to develop effective English language curriculums for enhancing communicative competence among learners.